Application of File Encryption and Decryption Using One Time Pad Algorithm - Muhammad Syahputra Novelan (Institute of Computer Science (IOCS), 2020)
In maintaining a system security, it is very important to pay attention to that, namely an authentication process. This process is carried out in order to ensure that users who access data or information are users who have the right and authority. In authentication, there are several methods, one of which is using data encryption techniques, namely cryptography. Cryptography is implemented in data and information by coding or hiding the original data so that only certain parts have a key that can access the data or information. This research will apply the One Time Pad (OTP) Algorithm based on android which includes data encryption and decryption which will be designed using Android Studio to carry out encryption of stored data or information. The data will be in the form of ciphertext so that the user gets an access key for the data or information. In making this application, it is hoped that it will be useful in maintaining data security and confidentiality.